Analysis of Modification in Synaptic Plasticity STDP (Spike Timing Dependent Plasticity) Model by Changing Intracellular Calcium Concentration - Shella Aisiyah Diva; Anis Yuniati (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2020)
Synapses are a junction between neurons that has a plastic property. Synaptic plasticity can be in the form of long-term potentiation (LTP) and long-term depression (LTD). The changes in intracellular calcium concentration can trigger LTP and LTD. Spike Timing Dependent Plasticity (STDP) is a modification of synapses that depend on the spike timing of pre-synapses and post-synapses neuron. In this study, we analyze the effects of intracellular calcium on the STDP phenomena based on Badoual’s model using mechanisms involving parameters such as calcium pumping, AMPA receptors, NMDA receptors, LTP enzymes, and LTD enzymes. In this model, a high calcium concentration will activate the LTP enzyme, while a low calcium concentration will activate the LTD enzyme, each of which will trigger the occurrence of LTP and LTD. The existence of LTP and LTD is the basis for the formation of the STDP. In this model, the parameters can be adjusted to obtain the STDP corresponding to experimental results where LTP is observed in the range between 0 < ∆t < 50ms, while LTD is observed at wider intervals between −150ms < ∆t <0. These parameters are related to the decay time of the NMDA receptor.